Evaluating the Psychological Impact of Forest Bathing: A Meta-Analysis of Emotional State Outcomes - Brahmaiah, Jyoti; Kishore, A.; Augustine, Alfred J.; Ramakrishnan, Ramya; Adiga, Usha; Hoogar, Praveen (International Journal of Statistics in Medical Research, 2024)
Background: Forest bathing, a therapeutic practice involving immersion in natural forest environments, has gained attention for its potential mental health benefits. This meta-analysis evaluates the impact of forest bathing on psychological parameters such as tension-anxiety, depression, anger-hostility, fatigue, confusion, and vigor. Methods: A meta-analysis was conducted on studies assessing forest bathing's effects on psychological states. Six studies were included, analyzing data using fixed and random effects models. Results: The analysis of six studies with 296 participants revealed a strong positive correlation between forest bathing and reduced tension-anxiety, with correlation coefficients of 0.634 (fixed effects) and 0.613 (random effects). Both models were statistically significant (p < 0.001), despite moderate to high heterogeneity (I² = 67.57%). For depression, five studies (277 participants) showed a significant reduction, with a stronger correlation in the random effects model (0.557) compared to the fixed effects model (0.432). Anger-hostility was similarly reduced, with high heterogeneity (I² = 90.12%) and correlation coefficients of 0.741 (fixed) and 0.767 (random). Fatigue, assessed in six studies (296 participants), also showed significant reductions, with moderate heterogeneity (I² = 45.16%). Confusion was moderately reduced (I² = 29.52%), with correlation coefficients of 0.339 (fixed) and 0.323 (random). Lastly, vigor showed a weak positive association, with a correlation coefficient of 0.269. Conclusion: The findings confirm the therapeutic potential of forest environments in promoting mental health. Given the observed positive effects, forest bathing could be integrated into public health strategies as a non-pharmacological intervention for stress and mood disorders.